Pola-pola Perilaku Eksekutif Berkaitn dengan Thapan Penawaran Opsi Saham: Uji Komprehensif di Sekitar Tanggal Hibah - Nur Fadjrih Asyik (The Indonesian Journal of Accounting Research, 2013)
This paper investigates the patterns of executive behavior to the each phase offer of stock option. Executives expected stock prices decreases prior to the grant date with a purpose to obtain the lower exercise and stock prices increases after the grant date with a purpose to obtain the larger gains. While, this study also investigats whether management manage factors of timing and option pricing model with identify the difference behavior of every step stock option offering. The amount of observation are 51 observations and the study finds that executives have ability to manage information around option grant date. The effect is stronger when executives release earnings before option grant date for period prior to ESOP. While, for period after ESOP, the effect is stronger with manage fair value factors are stock price volatility, but do not support for the risk-free interest rate and dividend yield. Based on phases of stock option offering, at prior to employee stock option plan, there are differences of influence of offer of the stock option on earnings management behavior at phase 1 and 2. However compared to phase 2, at phase 1 influence is the  sharper than phase 2. After ESOP, slope of phase 3 is sharper than slope of phase 1 and 2.